DETERMINANTS OF INTERNATIONAL DEMAND FOR TOURISM IN NIGERIA (2014)
The average international tourists arrival per thousand populations for the period 2000 to 2009 was 7 in Nigeria compared to 22 in Ghana. The major sources of these receipts were business tourists from France, United Kingdom and United State of America. Government efforts at increasing international tourism demand as an alternative source of non-oil revenue is yet to boost the country’s tourist arrivals. Previous studies have investigated the economic potential of Nigeria’s tourism, but paid little or no attention to explaining the factors responsible for the low demand. This study, therefore, examined the determinants of international demand for business and holiday tourism in Nigeria. The Gorman-Lancaster demand framework was used to derive the international business and holiday tourism demand models. The independent variables were prices, risks and infrastructure, in Nigeria and competitor countries, as well as tourists’ income. The competitor countries were Ghana, Benin, the Gambia and Togo with competitive weight of 27.7%, 25.0%. 25.0% and 22.2% respectively. The dependent variable was international tourist arrivals, which encompasses foreigners that visit Nigeria for a period between 1 day and 12 months, excluding transit passengers and foreigners in paid employment. Using quarterly data set for the period 2000Q1 to 2009Q4, panel fixed and random effects estimation techniques were utilised to estimate the parameters of the business and holiday tourism demand models from major origin countries considered; France, UK and US. The Hausman and Breuch-Pagan diagnostic tests were carried out to ascertain the efficacy of the model and the reliability of the results. The results were based on panel random effects model as supported by the diagnostic tests. All the variables were significant, for business and holiday tourism, at 1.0% p-value except prices which were not significant in the business tourism model. A 10.0% increase in income of tourist from UK was associated with 3.3% increase in the business tourism model and 0.5% increase in holiday tourism. An increase of 10.0% in risk level in Nigeria induced a 20.7% decrease in holiday tourism from US while a 10.0% increase in competitor countries’ risks led to an increase of 36.0% in business tourism from France. In the case of holiday tourism from the three origin countries, a 10.0% increase in prices in Nigeria was associated with a decrease of 0.4% in demand while a 10.0% increase in competitor countries’ prices was associated with a 0.7% increase. Irrespective of tourism types, a 10.0% increase in the Nigeria’s tourism infrastructure was associated with a 0.1% increase in demand from the three origin countries while a 10.0% increase in competitor countries’ infrastructure induced a decrease of 0.4%, 0.6% and 0.2% in tourism demand from UK, US and France, respectively. Improvements in tourism infrastructures and decrease in price level relative to competitor countries’ infrastructure and price levels significantly enhanced tourist inflow to Nigeria. Thus, the effectiveness of tourism policy in Nigeria is conditional on actions of other competitors’ countries. Nigeria should adopt segmented tourism marketing strategy in which high income groups in UK are targeted for business tourism.